(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Benign prostatic hyperplasia (BPH) is the most common benign tumour in men. About 50% of men at the age of 50 years develop BPH and about half of them report to the doctors with some form of lower urinary tract symptoms (LUTS). Objectives: To see the therapeutic effect of Tamsulosin on alternate day administration in comparison to daily dose for men who had been suffering from LUTS due to BPH. Materials and Methods: This clinical trial was carried out at Combined Military Hospital, Dhaka in a consecutive fashion for about 18 months. A total of 152 patients were selected from outpatient department and after assessing them through inclusion and exclusion criteria and grouped randomly in three groups Group-A (50 patients), Group-B (50 patients) and Group C (52 patients); all the patients were treated with Tablet Tamsulosin (0.4mg) daily for first three months. Then next 15 months they were treated as; Group-A received Tablet Tamsulosin (0.4mg) daily, Group-B received Tablet Tamsulosin (0.4mg) every alternate day and Group C received placebo Tablet (Folic acid 5 mg) daily. Data were collected at the beginning and end of 3rd month, 4th month, 7th month and 18th month of study, in the form of international prostate symptom score (IPSS), maximum urinary flow per second (Qmax) and post-voidal residue (PVR). Results: This study showed that at the initial three month, IPSS score declined in all three groups, Qmax improved and PVR reduced in all groups. In next phase of study; in Group-A patient there was progressive and significant improvement of all parameters (IPSS, Qmax and PVR) at the end of study. In Group-B patient also showed similar result at the end of study. In Group-C patient showed statistically significant difference in outcome in relation to Group-A and Group-B i.e. more in IPSS, less in Qmax and increase in PVR. Conclusion: With this study it is clearly evident that tamsulosin (0.4mg) therapy significantly improves symptoms of men suffering for LUTS due to BPH. And alternate day therapy having similar therapeutic outcome in relation to every day therapy. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 22-26